SOLVING OF THE PROBLEM OF THE BURDEN COMPOSITION OPTIMIZATION BY MEANS OF LINEAR PROGRAMMING - I. V. Rafalski; G. V. Dovnar; P. E. Lushchik (Литьë и металлургия, 2006)
The target setting of foundry charge calculations so as to minimize total cost of cast alloy was discussed. The linear programming methods were used to calculate the weight of charge metals which need to be melted to achieve a required composition of cast alloy. The software is developed for any foundry industry (ferrous, non-ferrous alloys production) where charges have to be assembled to achieve a required composition by weight and to minimize total cost of cast alloys.